Geriatric mental health care : lessons from a pandemic - Roca, Robert; Dugué, Micheline; Llorente, Maria D. (American Psychiatric Association Publishing, 2022)
"Geriatric Mental Health Care addresses the disproportionate impact that the COVID-19 pandemic has had on older adults with mental illness. Topics covered include inpatient geriatric psychiatry during a pandemic, telehealth models of care, health care staff concerns, and social determinants of health. The authors also explore the pandemic's effects on research and the economy, analyzing the impact of nonclinical factors on the broader clinical care effort. Geriatric Mental Health Care provides techniques that health care providers can use to overcome the challenges of the current pandemic-and prepare for the next one"--